Youth Organization Empowerment through Creative Entrepreneurship Business in the Village - Asrijal, Andi; Maspul, Kurniawan Arif; Seto, Agung Anggoro; Sain, Zohaib Hassan; Maq, Mumu Muzayyin (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
One of the youth groups that has a strategic role in village development is Youth Organization. This service aims to analyze youth empowerment through creative entrepreneurship in the village (district). This service method uses the Participatory Rural Appraisal (PRA) or participatory approach, including training, mentoring, and collaboration with relevant stakeholders. Implementation starts from coordination, activity socialization, activity implementation phase, program sustainability, and report preparation, to monitoring and evaluation. The results of this service are Creative Business Training, which has been carried out in a blinded manner, producing outputs in the form of the growth of a creative entrepreneurial spirit, new products typical of the people of the Dekai District of Papua, handbooks, training modules, progress reports, final reports, of course, this is expected to have a principle of usefulness.